Factors Related to Willing Mom for Post Placenta IUD Installation - Aswan, Yulinda; Dewi , Sri Sartika Sari; Wahyuni , Iin (PT Inovasi Pratama Internasional, 2022)
The most ideal contraception for postpartum mothers childbirth and breastfeeding is not suppressing the production of breast milk, namely the Intra Uterine Device (IUD). The purpose of this study was to determine the factors associated with the mother's willingness to insert a post-placental IUD. This research is a quantitative research using the dynamics of correlation between phenomena with a cross sectional study design . The population in this study were all pregnant women over 30 weeks in April. The sample of this research was 47 pregnant women with gestational age above 30 weeks which were taken from the total sampling technique . Based on the results of the chi square statistical test with a 95% confidence level (α = 0.05) it was found that there was a significant relationship between knowledge (P 0.000), attitude (P 0.002), husband's support (P 0.001), mother's interest (P 0.001) , the support of health workers (P 0.001) with the mother's willingness to insert a post-placental IUD. It is hoped that mothers will be able to participate in the use of contraceptives.